Medikamentöse Therapie der Sepsis = Pharmacological therapy of sepsis - Thiel, Manfred; Bardenheuer, Hubert J. (Der Anaesthesist, 1994)
The interaction of immunocompetent cells with the vascular endothelium is of prime importance for the development of septic multiple organ failure. There is evidence from in-vitro studies that the methylxanthine derivative pentoxifylline can attenuate the extent of inflammatory reactions by amplification of cell-derived endogenous regulators. For instance, pentoxifylline potentiates the anti-inflammatory actions of adenosine, prostacycline, and prostaglandins of the E series by its synergistic action on intracellular cyclic AMP. By this mechanism, pentoxifylline inhibits the oxygen-radical production of polymorphonuclear leukocytes, the aggregation of platelets, disseminated intravascular coagulation, and the production of cytokines. Consequently, pentoxifylline improves perfusion in the microcirculation as well as tissue oxygenation. Further studies will clarify whether the promising results obtained with pentoxifylline in experimental septic shock will be confirmed under clinical conditions.
Gesehen am 14.11.2023